Positive plate and battery
By providing a first positive electrode active layer including a first lithium manganese iron phosphate material and a carbon nanotube in the positive electrode sheet of the lithium-ion battery, and cooperating with the second positive electrode active layer, the battery needle stab safety performance in the prior art is solved The problem of difficulty in taking into account both energy density and high safety performance is achieved.
Patent Information
- Application Number
- CN202411742062.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
AI Technical Summary
While improving the needle-punching safety performance of lithium-ion batteries, it is difficult to maintain the high energy density of the battery. Especially in large-capacity and high-fold ternary system batteries, the effect of insulating particles undercoating seems to be very short of the effect. Moreover, the insulating particles have no electrochemical activity, which reduces the energy density of the battery.
By providing a first positive electrode active layer between the positive electrode current collector and the second positive electrode active layer, the layer includes a first lithium manganese iron phosphate material and a first conductive agent, the carbon nanotubes are used as the conductive agent to enhance the conductivity, and through The coordinated cooperation of the second positive electrode active layer includes a ternary material and a second lithium manganese iron phosphate material to improve thermal stability and isolation effect.
It achieves the battery's needle-punch safety performance while maintaining high energy density, reduces the risk of thermal runaway, and improves the overall safety performance of the battery.
Smart Images

Figure CN119480905A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet and a battery comprising the positive electrode sheet. Background Art
[0002] With the rapid development of lithium-ion battery technology, its application in electric vehicles, smart grid energy storage systems and portable electronic devices is becoming more and more extensive, which puts more stringent requirements on the comprehensive performance of batteries. Among them, battery safety performance, energy density and cycle stability are three key indicators that are directly related to the market competitiveness and user experience of products. Especially in terms of battery safety performance, the needle penetration test is an important means to evaluate battery safety under extreme working conditions, and its performance optimization has become the focus of attention inside and outside the industry. Summary of the invention
[0003] In order to improve the overcharge performance of the battery, the industry generally adopts the method of adding lithium manganese iron phosphate to the ternary material (such as Figure 4 As shown in FIG. 1 , the positive electrode sheet includes a positive electrode current collector 1 and a positive electrode active material layer 7 located on the surface of the positive electrode current collector 1, and the positive electrode active material 7 includes a lithium manganese iron phosphate material 71 and a ternary material 72). However, this will make the battery's acupuncture safety performance not guaranteed. The industry further adopts a method of coating an insulating particle primer on the surface of the positive electrode sheet current collector (such as Figure 1 As shown, the positive electrode sheet includes a positive electrode current collector 1, an undercoat layer 4 and a positive electrode active material layer 5, the undercoat layer 4 is located between the positive electrode current collector 1 and the positive electrode active material layer 5, the undercoat layer 4 includes insulating particles, and the positive electrode active material layer 5 includes a lithium manganese iron phosphate material 51 and a ternary material 52; Figure 2As shown, the positive electrode sheet includes a positive electrode collector 1, an undercoat layer 4 and a positive electrode active material layer 6, the undercoat layer 4 is located between the positive electrode collector 1 and the positive electrode active material layer 6, the undercoat layer 4 includes insulating particles, and the positive electrode active material layer 6 includes a ternary material 61). This method effectively reduces the risk of thermal runaway caused by short circuit by physically isolating the direct contact between the debris generated by the current collector during the acupuncture process and the negative electrode material, thereby improving the acupuncture safety of the battery. However, when the battery has a large capacity (≥5Ah) and a large number of folds (≥20 folds), the effect of applying this method seems to be insufficient. Due to the complex internal structure of these two types of batteries and the large particle size and poor thermal stability of the ternary materials, when the battery is punctured, the insulating particle basecoat layer is difficult to fully and effectively cover all potential short-circuit points. The appearance of short-circuit points causes the ternary materials to generate heat rapidly and reach the thermal decomposition temperature of this type of material, resulting in thermal runaway, resulting in limited improvement in puncture performance. In addition, the method of coating the insulating particle basecoat layer on the surface of the positive electrode current collector greatly reduces the energy density of the battery due to the inert electrochemical activity of the insulating particles. Therefore, it is impossible to improve the battery puncture safety while ensuring the battery energy density.
[0004] In order to solve the above technical problems existing in the prior art, the present invention provides a positive electrode sheet and a battery including the positive electrode sheet. The battery including the positive electrode sheet of the present invention can improve the battery's acupuncture safety while ensuring a high battery energy density.
[0005] To achieve the above-mentioned objectives, the first aspect of the present invention provides a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode active material layer located on one side or both sides of the positive electrode collector, the positive electrode active material layer comprises a first positive electrode active layer and a second positive electrode active layer, the first positive electrode active layer is located between the positive electrode collector and the second positive electrode active layer, the first positive electrode active layer comprises a first lithium iron manganese phosphate material and a first conductive agent, the first conductive agent comprises carbon nanotubes; the second positive electrode active layer comprises a ternary material and a second lithium iron manganese phosphate material.
[0006] A second aspect of the present invention provides a battery, comprising a separator and the positive electrode sheet according to the first aspect of the present invention.
[0007] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0008] The positive electrode sheet of the present invention includes a first positive electrode active layer located between the positive electrode collector and the second positive electrode active layer, the first positive electrode active layer includes a first lithium iron manganese phosphate material and a first conductive agent, the first lithium iron manganese phosphate material has excellent thermal stability, and can play the same puncture protection effect as insulating particles, that is, when puncture occurs, the particles of the first lithium iron manganese phosphate material wrap the cross-section layer of the aluminum foil current collector, effectively preventing the positive electrode collector (aluminum foil) and the negative electrode sheet from short-circuiting to generate a large amount of heat and cause thermal runaway. The advantage of the first lithium iron manganese phosphate material is that it has electrochemical activity and high capacity. Therefore, compared with the setting of the insulating particle bottom coating, the setting of the first positive electrode active layer will not only not affect the energy density of the battery, but also because the first lithium iron manganese phosphate material will exert its capacity, it can also improve the energy density of the battery. At the same time, it cooperates with the second positive electrode active layer including the second lithium iron manganese phosphate material and the ternary material. Since the second lithium iron manganese phosphate material has a frame structure, the frame structure makes the second lithium iron manganese phosphate material have high thermal stability, and failure stability is not easy to achieve, which reduces the risk of thermal runaway of the battery. At the same time, after the ternary material is mixed with the second lithium iron manganese phosphate material, the second lithium iron manganese phosphate material can separate the ternary material with poor stability, thereby avoiding heat accumulation of the ternary material when the battery is punctured, reducing the heat generation of the ternary material, ensuring that the ternary material does not spread heat when the battery is punctured, reducing the risk of battery fire, and improving the safety performance of the battery. Therefore, through the coordinated cooperation of the first positive electrode active layer and the second positive electrode active layer, the battery has both high energy density and high safety performance. In addition, since the voltage platform of the second lithium manganese iron phosphate material is similar to the voltage platform of the ternary material, the stability and reliability of the battery performance can be guaranteed.
[0009] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0010] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Shown is a schematic diagram of the positive electrode sheet of Comparative Example 2.
[0012] Figure 2 Shown is a schematic diagram of the positive electrode sheet of Comparative Example 3.
[0013] Figure 3 FIG. 4 is a schematic diagram of a positive electrode sheet according to an embodiment of the present invention.
[0014] Figure 4 Shown is a schematic diagram of the positive electrode sheet of Comparative Example 1.
[0015] Figure 5 Shown is a SEM image of the surface of the coating layer including titanium dioxide of the positive electrode sheet of Comparative Example 2.
[0016] Figure 6 Shown is a SEM image of the surface of the first positive electrode active layer of Example 1.
[0017] Figure 7 Shown Figure 6 Magnified image of .
[0018] Figure 8 Shown is a SEM image of the surface of the positive electrode sheet after rolling in Example 1.
[0019] Fig. 9 Shown is a SEM image of the surface of the positive electrode sheet of Comparative Example 1 after rolling.
[0020] Fig.10 The SEM image of the positive electrode surface after rolling in comparative example 2 is shown.
[0021] Fig.11 Shown is a SEM image of the surface of the positive electrode sheet of Comparative Example 6 after rolling.
[0022] Fig.12 Shown is a SEM image of the cross section of the positive electrode sheet of Example 1.
[0023] Fig.13 Shown is a SEM image of the cross section of the positive electrode sheet of Comparative Example 2.
[0024] Fig.14 Shown is a SEM image of the cross section of the positive electrode sheet of Comparative Example 1.
[0025] Fig.15 Shown is a SEM image of the cross section of the positive electrode sheet of Comparative Example 6. DETAILED DESCRIPTION
[0026] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.
[0027] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.
[0028] A first aspect of the present invention provides a positive electrode sheet, wherein the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer located on one side or both sides of the positive electrode collector, the positive electrode active material layer includes a first positive electrode active layer and a second positive electrode active layer, the first positive electrode active layer is located between the positive electrode collector and the second positive electrode active layer, the first positive electrode active layer includes a first lithium iron manganese phosphate material and a first conductive agent, the first conductive agent includes carbon nanotubes; the second positive electrode active layer includes a ternary material and a second lithium iron manganese phosphate material.
[0029] like Figure 3 As shown, the positive electrode sheet includes a positive electrode collector 1 and a positive electrode active material layer located on one side or both sides of the positive electrode collector 1, the positive electrode active material layer includes a first positive electrode active layer 2 and a second positive electrode active layer 3, and the first positive electrode active layer 2 is located between the positive electrode collector 1 and the second positive electrode active layer 3. The second positive electrode active layer 3 includes a ternary material 32 and a second lithium manganese iron phosphate material 31.
[0030] The positive electrode sheet of the present invention includes a positive electrode collector, a second positive electrode active layer and a first positive electrode active layer between the positive electrode collector and the second positive electrode active layer, the first positive electrode active layer includes a first lithium iron manganese phosphate material, when the battery is punctured, the first lithium iron manganese phosphate material can wrap the cross section of the positive electrode collector (such as aluminum foil), thereby effectively isolating the direct contact between the cross section of the positive electrode collector and the negative electrode active material, and when the first lithium iron manganese phosphate material in the first positive electrode active layer fails to completely wrap the cross section of the positive electrode collector, the second lithium iron manganese phosphate in the second positive electrode active layer can further wrap the cross section of the positive electrode collector, thereby further improving the thermal temperature resistance of the battery under extreme conditions such as puncture, thereby reducing the risk of thermal runaway of the battery and improving the safety performance of the battery; and the first lithium iron manganese phosphate material has electrochemical activity and has a high capacity, the presence of the first positive electrode active layer can not only improve the safety of the battery The performance is improved, and the volume energy density of the battery will not be reduced due to the setting of the first positive electrode active layer. On the contrary, the energy density of the battery will be increased. At the same time, through the coordinated cooperation of the first positive electrode active layer and the second positive electrode active layer including the second lithium iron manganese phosphate material and the ternary material, the second lithium iron manganese phosphate material and the ternary material are blended, and the second lithium iron manganese phosphate material with higher thermal stability can isolate the ternary material with poor thermal stability and high heat generation, reduce the occurrence of heat accumulation, and make it difficult for the temperature to reach the thermal decomposition temperature of the ternary material when the puncture occurs, thereby ensuring that the ternary material is not easy to fail, and even if the thermal decomposition temperature of the ternary material is reached, the second lithium iron manganese phosphate material with higher thermal stability isolates the ternary material, which can also avoid heat accumulation of the ternary material, ensuring that the ternary material does not spread heat when the battery is punctured, reducing the risk of battery fire, so that the battery has both high energy density and high safety performance. At the same time, since the first positive electrode active layer located between the positive electrode current collector and the second positive electrode active layer includes a first conductive agent, and the first conductive agent includes carbon nanotubes, it is ensured that the active material of the second positive electrode active layer realizes electron transmission through the conductive path formed by the carbon nanotubes, thereby ensuring the electrical performance of the battery.
[0031] In the present invention, by providing a first positive electrode active layer between the positive electrode current collector and the second positive electrode active layer, and making the first positive electrode active layer and the second positive electrode active layer both comprise lithium iron manganese phosphate material, compared with the prior art, the battery can have both the advantages of high energy density and high safety performance. In order to further improve the effect, one or more of the technical features may be further optimized.
[0032] In one example, the first positive electrode active layer also includes a first binder, and the positive electrode sheet satisfies the following relationship: 27.8≤(D1*L) / F≤400 (for example, 27.8, 50, 100, 150, 200, 250, 300, 350 or 400), wherein D1 is the median particle size Dv50 of the first lithium manganese iron phosphate material, in μm, L is the length of the carbon nanotube, in μm, and F is the peeling force between the first positive electrode active layer and the positive electrode current collector, in kgf.
[0033] Controlling the positive electrode sheet so that it satisfies the above relationship can make the first lithium iron manganese phosphate material and the carbon nanotubes dispersed evenly, improve the cycle performance of the battery, and connect the first lithium iron manganese phosphate material into a three-dimensional conductive network through carbon nanotubes and carbon black, thereby increasing the charge transfer speed of the first positive electrode active layer, improving the conductivity of the first positive electrode active layer, and improving the high-rate charge and discharge cycle performance of the battery. At the same time, it is ensured that the first positive electrode active layer can be firmly attached to the surface of the positive electrode collector, further improving the cycle performance and safety performance of the battery. When (D1*L) / F<27.8, it means that at least one of the median particle size of the first lithium iron manganese phosphate and the length of the carbon nanotubes in the first positive electrode active layer is too small, or the peeling force between the first positive electrode active layer and the positive electrode collector is too high. When the median particle size of the first lithium iron manganese phosphate and / or the length of the carbon nanotubes in the first positive electrode active layer are small, the battery impedance will increase and the polarization will increase, resulting in a significant deterioration in the rate performance and cycle performance of the battery. When the peeling force between the first positive electrode active layer and the positive electrode collector is too high, the cyclic stress between the positive electrode collector and the first positive electrode active layer will increase, resulting in microcracks in the first positive electrode active layer, and broken and delaminated, thereby affecting the deintercalation and migration of lithium ions, resulting in battery capacity decay. When (D1*L) / F>400, it means that at this time at least one of the particle size of the first lithium iron manganese phosphate and the length of the carbon nanotubes in the first positive electrode active layer is too large, or the peeling force between the first positive electrode active layer and the positive electrode collector is too small. When at least one of the particle size of the first lithium iron manganese phosphate and the length of the carbon nanotubes in the first positive electrode active layer is too large, the slurry stability of the first positive electrode active layer will be poor, the consistency of the first positive electrode active layer after coating will be poor, and the local position impedance will be significantly increased, resulting in poor battery cycle performance; when the peeling force between the first positive electrode active layer and the positive electrode collector is too small, the adhesion between the first positive electrode active layer and the positive electrode collector is insufficient, and the first positive electrode active layer cannot effectively wrap the aluminum foil cross-section layer when acupuncture occurs, resulting in poor acupuncture safety performance.
[0034] In the present invention, the length L of the carbon nanotubes can be obtained by testing using the following method: using a scanning electron microscope to test, within a range of 20 μm×20 μm, counting the lengths of the carbon nanotube bundles, and taking the average length of all carbon nanotube bundles in the region as the carbon nanotube length L.
[0035] In one example, D1 is 0.2 μm-2 μm (eg, 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, or 2 μm).
[0036] In one example, D1 is 0.5 μm-1.5 μm.
[0037] In one example, L is 5 μm-100 μm (eg, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, or 100 μm).
[0038] In one example, L is 50 μm-80 μm.
[0039] In one example, D1 is 0.2μm-2μm, and L is 5μm-100μm. Controlling D1 and L within the above range can make the first lithium manganese iron phosphate material and carbon nanotubes evenly dispersed in the first positive electrode active layer, thereby ensuring the uniformity of the coating of the first positive electrode active layer. When D1 is higher than 2μm and / or L is higher than 100μm, the thickness of the first positive electrode active layer increases, affecting the energy density of the battery, and because the conductivity of the first lithium manganese iron phosphate material is low, the resistivity of the first positive electrode active layer increases, affecting the cycle performance of the battery. When D1 is lower than 0.2μm and / or L is lower than 5μm, the particle size is too small and agglomeration is likely to occur, resulting in uneven mixing of the first positive electrode active layer, increased impedance at local locations, and reduced cycle performance of the battery.
[0040] In one example, D1 is 0.5 μm-1.5 μm, and L is 50 μm-80 μm.
[0041] In one example, the peeling force F between the first positive electrode active layer and the positive electrode current collector is ≥0.3 kgf (eg, 0.3 kgf, 0.4 kgf, 0.5 kgf, 0.6 kgf, 0.7 kgf, 0.8 kgf, 0.9 kgf or 1 kgf).
[0042] In one example, the peeling force F between the first positive electrode active layer and the positive electrode current collector is 0.3 kgf-0.9 kgf.
[0043] According to a specific implementation, D1 is 0.5 μm-1.5 μm, L is 50 μm-80 μm, F is 0.3 kgf-0.9 kgf, and the positive electrode sheet satisfies the following relationship: 27.8≤(D1*L) / F≤400.
[0044] In one example, the weight content w1 of carbon nanotubes in the first positive electrode active layer is 0.2%-3% (for example, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%). Controlling w1 within the above range enables the first lithium manganese iron phosphate material to connect to form a three-dimensional conductive network, thereby improving the conductivity of the first positive electrode active layer and improving the high-rate charge and discharge cycle performance of the battery. When w1 is lower than 0.2%, the content of carbon nanotubes is too low to form an effective conductive network; when w1 is higher than 3%, the content of carbon nanotubes is too high, and the slurry forming the first positive electrode active layer is too viscous, affecting the coating uniformity of the first positive electrode active layer.
[0045] In one example, w1 is 0.5%-2%.
[0046] In one example, the first positive active layer further includes a first binder, which includes one or more of polyvinylidene fluoride, acrylic acid-modified polyvinylidene fluoride, carboxylic acid-modified polyvinylidene fluoride, polyacrylic acid, polyacrylic acid copolymer, polymethyl methacrylate, carboxylated polyvinylidene fluoride, polyvinyl alcohol and polyimide.
[0047] In one example, the weight content w3 of the first binder in the first positive electrode active layer is 2%-7% (for example, 2%, 3%, 4%, 5%, 6% or 7%). Controlling w3 within the above range can ensure that the first positive electrode active layer can be firmly attached to the surface of the positive electrode current collector, thereby ensuring the safety of needle puncture while improving the cycle performance. When w3 is less than 2%, the bonding force of the first positive electrode active layer is insufficient, affecting the safety performance of the battery during needle puncture.
[0048] In one example, w3 is 2.5%-5%.
[0049] In one example, the first conductive agent further includes a conductive material, and the conductive material includes one or more of conductive carbon black, acetylene black, and Ketjen black.
[0050] In one example, the weight ratio of the conductive material to the carbon nanotube is (0.5-20):1 (for example, 0.5:1, 1:1, 3:1, 5:1, 8:1, 10:1, 13:1, 15:1, 18:1 or 20:1). By controlling the weight ratio of the conductive material to the carbon nanotube within the above range, an effective three-dimensional conductive network can be formed, and the conductive material and the carbon nanotube can work together to provide a good electron transfer path, thereby enhancing the conductivity of the first positive electrode active material layer. When the weight ratio of the conductive material to the carbon nanotube is lower than 0.5:1, the amount of the conductive material is insufficient to form an effective three-dimensional conductive network with the carbon nanotube, resulting in reduced connectivity of the conductive network, thereby affecting the overall conductive performance of the material; when the weight ratio of the conductive material to the carbon nanotube is higher than 20:1, the weight of the conductive material is too much, and the conductive material particles will agglomerate to cause uneven dispersion. In addition, too much conductive material will also hinder the effective connection between the carbon nanotubes and destroy the integrity of the three-dimensional conductive network.
[0051] In one example, the ratio of the weight of the conductive material to the weight of the carbon nanotubes is (1-7):1.
[0052] In one example, the weight ratio of the ternary material to the weight ratio of the second lithium iron manganese phosphate material is (1-4):1 (for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1). By controlling the weight ratio of the ternary material to the weight ratio of the second lithium iron manganese phosphate material to be within the above range, the second lithium iron manganese phosphate material can isolate the ternary material to avoid heat accumulation in the ternary material, reduce the heat generated by the rapid accumulation of the ternary material during acupuncture, thereby avoiding battery runaway, and the framework structure of the second lithium iron manganese phosphate material makes it have higher thermal stability and lower thermal runaway risk. During the acupuncture process, the second lithium iron manganese phosphate material can move in the direction of acupuncture with the needle and wrap the positive electrode current collector section, thereby improving the acupuncture safety of the battery. When the weight ratio of the ternary material to the weight ratio of the second lithium manganese iron phosphate material is lower than 1:1, the proportion of the second lithium manganese iron phosphate material is too high, which can improve the safety performance of the battery, but will significantly reduce the energy density of the battery, resulting in the battery being unable to meet the high requirements of the driving range of applications such as electric vehicles. At the same time, the second lithium manganese iron phosphate material itself has poor conductivity, which causes the battery to produce a large polarization phenomenon and energy loss during the charging and discharging process, thereby reducing the cycle life and charging and discharging performance of the battery. When the weight ratio of the ternary material to the weight ratio of the second lithium manganese iron phosphate material is higher than 4:1, the proportion of the ternary material is too high, which can further improve the energy density of the battery, but because the ternary material is prone to thermal runaway and fire and explosion safety accidents under extreme conditions such as high temperature, overcharge or over discharge, it will affect the safety performance of the battery, and will also increase the cost of the battery and reduce the economy of the battery.
[0053] According to a specific embodiment, the ratio of the weight of the conductive material to the weight of the carbon nanotubes is (1-2):1, the ratio of the weight of the ternary material to the weight of the second lithium manganese iron phosphate material is (1-4):1, and the positive electrode sheet satisfies the following relationship: 27.8≤(D1*L) / F≤400.
[0054] In one embodiment, the ternary material comprises a chemical formula of Li(Ni x Co y Mn z )O2 material, wherein x+y+z=1, 0.8≤x<1 (for example, 0.8, 0.83, 0.85, 0.88, 0.9, 0.3, 0.95, 0.98 or 0.99), 0<y<0.2 (for example, 0.05, 0.1, 0.13, 0.15, 0.18 or 0.19), 0<z<0.2 (for example, 0.05, 0.1, 0.13, 0.15, 0.18 or 0.19).
[0055] In the chemical formula Li(Ni x Coy Mn z )The elements in O2 conform to the principle that the algebraic sum of the positive and negative valences of the elements in the compound is zero.
[0056] The chemical formula satisfies 0.8≤x<1, indicating that the ternary material is a high-nickel ternary material. The high-nickel ternary material has a higher gram capacity, but the high-nickel ternary material has poor cycle performance and poor thermal stability.
[0057] In one example, the surface of the ternary material has a coating layer, and the coating layer includes a metal oxide. In order to overcome the problems of poor cycle performance and poor thermal stability of high-nickel ternary materials, the ternary material is coated with a metal oxide.
[0058] The metal oxide may include Al2O3, ZrO2, WO3 and SrO. Among them, Al element has excellent thermal stability, which can prevent the ternary material from directly contacting with the electrolyte under high voltage, causing oxidation and heat generation; W element has good electrical conductivity and chemical stability as well as excellent thermal stability, which can not only improve the electron transmission efficiency of the ternary material, but also help to improve the thermal safety of the ternary material; Zr element and Sr element can affect the lattice parameters and crystal structure stability of the ternary material, which helps to reduce the phase change and structural degradation of the ternary material, thereby improving the cycle life and stability of the battery.
[0059] In one example, the ternary material satisfies the following relationship: 0.16≤A*C / (B*D)≤0.8, wherein A is the weight content of the element Al in the ternary material having a coating layer, in ppm, B is the weight content of the element Zr in the ternary material having a coating layer, in ppm, C is the weight content of the element W in the ternary material having a coating layer, in ppm, and D is the weight content of the element Sr in the ternary material having a coating layer, in ppm.
[0060] Controlling the ternary material to satisfy the above relationship can improve the transmission efficiency of electrons in the ternary material and the diffusion rate of lithium ions in the ternary material, improve the electrochemical performance of the ternary material, and Al2O3 and WO3 have good thermal stability, which can prevent the ternary material from thermal runaway and thermal runaway at high temperatures. At the same time, it can also reduce the interface resistance between the ternary material and the metal oxide coating layer, thereby improving the cycle stability and safety performance of the ternary material. When A*C / (B*D)<0.16, the content of Al2O3 and WO3 is low, and the ternary material is prone to phase change and thermal runaway at high temperatures; when Al2O3 and WO3>0.8, the content of ZrO2 and SrO is relatively reduced, and the cycle stability and structural stability of the ternary material are reduced.
[0061] In one example, A ranges from 800 ppm to 1200 ppm (eg, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, or 1200 ppm).
[0062] In one example, B ranges from 2500 ppm to 3500 ppm (eg, 2500 ppm, 2800 ppm, 3000 ppm, 3300 ppm, or 3500 ppm).
[0063] In one example, C ranges from 700 ppm to 1000 ppm (eg, 700 ppm, 800 ppm, 900 ppm, or 1000 ppm).
[0064] In one example, Dppm is 600ppm-1000ppm (eg, 600ppm, 700ppm, 800ppm, 900ppm, or 1000ppm).
[0065] In one example, A ppm is 800ppm-1200ppm, B ppm is 2500ppm-3500ppm, C ppm is 700ppm-1000ppm, D ppm is 600ppm-1000ppm, and the ternary material satisfies the following relationship: 0.16≤A*C / (B*D)≤0.8.
[0066] In one example, the ternary material includes a single crystal structure. Generally, the ternary material with a polycrystalline structure exists in the form of micron-level agglomerates, and there are a large number of grain boundaries inside the agglomerates. During the battery charging and discharging process, due to the anisotropic lattice change, the ternary material with a polycrystalline structure is prone to grain boundary cracking, resulting in secondary particles being broken, which leads to a rapid increase in side reactions, an increase in battery impedance, and a rapid decrease in performance. The ternary material with a single crystal structure can reduce grain boundaries and the occurrence of side reactions, thereby improving the battery's cycle performance, and is also conducive to increasing the compaction density of the positive electrode sheet, thereby increasing the battery's energy density.
[0067] In one example, the median particle size Dv50 of the ternary material is 2 μm-5 μm (eg, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm).
[0068] In one example, the median particle size Dv50 of the second lithium iron manganese phosphate material is 0.5 μm-1.5 μm (e.g., 0.5 μm, 0.8 μm, 1 μm, 1.2 μm or 1.5 μm). Since the resistivity of the lithium iron manganese phosphate material is relatively large, controlling Dv50 within the above range can effectively reduce the resistivity of the lithium iron manganese phosphate material.
[0069] In one example, the first lithium iron manganese phosphate material and the second lithium iron manganese phosphate material are the same or different, and each independently comprises a chemical formula of LiFe a Mn (1-a) PO4 material. Since the first lithium iron manganese phosphate material and the second lithium iron manganese phosphate material are both lithium iron manganese phosphate materials, the expressions "first" and "second" are only for distinction, and are collectively referred to as "lithium iron manganese phosphate materials" when no distinction is required. The Mn element in the above chemical formula can increase the voltage platform of the lithium iron manganese phosphate material, thereby increasing the energy density of the battery.
[0070] In the chemical formula LiFe a Mn (1-a) The elements in PO4 conform to the principle that the algebraic sum of the positive and negative valences of the elements in the compound is zero.
[0071] Wherein, 0<a<1 (for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.99). Controlling a within the above range and making the content of Mn element within a suitable range can increase the gram capacity of the lithium manganese iron phosphate material, and at the same time can also improve the structural stability of the lithium manganese iron phosphate material, thereby extending the cycle life of the battery, and also can improve the safety performance of the battery. When a is 1, the content of Mn element is too high, and the Jan-Taylor effect will occur. The manganese in the lithium manganese iron phosphate material will dissolve during the charging and discharging process, and the structural stability of the lithium manganese iron phosphate material will deteriorate. As the cycle proceeds, the internal resistance of the battery increases, and the polarization increases, which not only affects the cycle performance of the battery, but even causes the battery safety performance to deteriorate as the cycle proceeds.
[0072] In one example, 0.2≤a≤0.4.
[0073] In one example, the first lithium iron manganese phosphate and / or the second lithium iron manganese phosphate material includes an olivine structure.
[0074] In one example, the surface of the first lithium iron manganese phosphate material and / or the second lithium iron manganese phosphate material includes a carbon coating layer. Since the resistivity of the lithium iron manganese phosphate material is relatively large, the carbon coating layer can effectively reduce the resistivity of the lithium iron manganese phosphate material.
[0075] In one example, the first lithium iron manganese phosphate material and / or the second lithium iron manganese phosphate material include doping elements, and the doping elements include Mg, Ti and Zr. The Mg element can stabilize the crystal structure of the lithium iron manganese phosphate material, improve the stability of the lithium iron manganese phosphate material, and thus improve the cycle stability of the battery. The Ti element can improve the electronic conductivity of the lithium iron manganese phosphate material and improve the rate performance of the battery. The Zr element helps to refine the grains and improve the structural stability of the lithium iron manganese phosphate material, thereby extending the cycle life of the battery.
[0076] In one example, based on the total weight of the first lithium iron manganese phosphate material including the carbon coating layer, the weight content of the carbon coating layer is 1%-3% (eg, 1%, 1.5%, 2%, 2.5% or 3%).
[0077] In one example, based on the total weight of the second lithium manganese iron phosphate material including the carbon coating layer, the weight content of the carbon coating layer is 1%-3% (eg, 1%, 1.5%, 2%, 2.5% or 3%).
[0078] In one example, based on the total weight of the first lithium manganese iron phosphate material including the doping element, the weight content of the Mg element is 500ppm-6000ppm (for example, 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm or 6000ppm).
[0079] In one example, based on the total weight of the first lithium manganese iron phosphate material including the doping elements, the weight content of the Mg element is 1500ppm-4500ppm (for example, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm or 4500ppm), the weight content of the Ti element is 400ppm-1000ppm (for example, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm or 1000ppm), and the weight content of the Zr element is 200ppm-700ppm (for example, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm or 700ppm).
[0080] In one example, based on the total weight of the second lithium manganese iron phosphate material including the doping element, the weight content of the Mg element is 500ppm-6000ppm (for example, 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm or 6000ppm).
[0081] In one example, based on the total weight of the second lithium manganese iron phosphate material including the doping element, the weight content of the Mg element is 1500ppm-4500ppm (for example, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm or 4500ppm), the weight content of the Ti element is 400ppm-1000ppm (for example, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm or 1000ppm), and the weight content of the Zr element is 200ppm-700ppm (for example, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm or 700ppm).
[0082] In one example, based on the total weight of the first positive electrode active layer, the weight content of the first lithium iron manganese phosphate material is 84%-97.6% (for example, 84%, 85%, 88%, 90%, 93%, 95% or 97.6%), the weight content of the first conductive agent is 0.4%-9% (for example, 0.4%, 1%, 3%, 5%, 8% or 9%), and the weight content of the first binder is 2%-7% (for example, 2%, 3%, 4%, 5%, 6% or 7%).
[0083] In one example, based on the total weight of the first positive electrode active layer, the weight content of the first lithium manganese iron phosphate material is 90.5%-96.5%, the weight content of the first conductive agent is 1%-4.5%, and the weight content of the first binder is 2.5%-5%.
[0084] In one example, the surface resistance of the first positive electrode active layer is 0.01Ω-0.4Ω (eg, 0.01Ω, 0.05Ω, 0.1Ω, 0.2Ω, 0.3Ω or 0.4Ω).
[0085] In the present invention, the surface resistance of the first positive electrode active layer can be tested by the following method: cut the coated and dried first positive electrode active layer sheet (first positive electrode active layer and positive electrode current collector) into 5cm*5cm small pieces, 10 pieces, and place them in the middle of the ACCFilm film resistance meter probe, click the start test on the software, press the upper probe down, and when the probe contacts and triggers the recording condition, the test is completed, and 10 data are recorded repeatedly, and the average value is taken as the surface resistance of the first positive electrode active layer.
[0086] In one example, the peeling force of the first positive electrode active layer is ≥0.3 kgf.
[0087] In the present invention, the peeling force can be tested by the following method: cut the first positive electrode active layer sheet (first positive electrode active layer and positive electrode current collector) after drying into 400mm long and 25mm wide, and cut into 3 strips. Paste the cut first positive electrode active layer sheet on the steel plate (double-sided tape is pasted on the steel plate), and then roll it with a 2kg steel roller for 3 times. Insert the steel plate with the fixed electrode sheet into the lower clamp of the tensile machine and fix it vertically. Insert the un-adhesive electrode sheet into the upper clamp of the tensile machine and fix it at 180° with the electrode sheet of the lower clamp. Start the tensile machine and start the test. The test machine automatically records the applied force and displacement and other data. The average of the data of the 3 bottom coating sheets is taken as the peeling force of the first positive electrode active layer.
[0088] In one example, the thickness of the first positive electrode active layer is 2 μm-10 μm (eg, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm).
[0089] In one example, the surface resistance of the first positive electrode active layer is 0.01Ω-0.4Ω, the peeling force of the first positive electrode active layer is ≥0.3kgf, and the thickness of the first positive electrode active layer is 2μm-10μm. By controlling the weight content range of the first lithium iron manganese phosphate material, the first conductive agent and the first binder in the first positive electrode active layer, the surface resistance, peeling force and thickness of the first positive electrode active layer meet the above ranges, which can ensure that electrons are transmitted quickly and efficiently during the charging and discharging process, reduce energy loss, and thus improve the high-rate charging and discharging cycle performance of the battery; at the same time, the first positive electrode active layer has good adhesion to the positive electrode collector, and the particles in the first positive electrode active layer are not easy to peel off during acupuncture, thereby improving the acupuncture safety performance of the battery, and because the compaction density of lithium iron manganese phosphate is relatively small, the first positive electrode active layer can meet the requirements of acupuncture safety performance and enable the battery to have a good energy density within a suitable thickness range.
[0090] In one example, the second positive electrode active layer further includes a second conductive agent and a second binder.
[0091] In one example, the second conductive agent includes one or more of carbon nanotubes, carbon black, Ketjen black, and acetylene black.
[0092] In one example, the second binder includes one or more of polyvinylidene fluoride, acrylic acid-modified polyvinylidene fluoride, carboxylic acid-modified polyvinylidene fluoride, polyacrylic acid, polyacrylic acid copolymer, polymethyl methacrylate, and polyimide.
[0093] In one example, based on the total weight of the second positive electrode active layer, the sum of the weight contents of the second lithium manganese iron phosphate material and the ternary material is 75%-98.9% (for example, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93%, 95% or 98.9%), the weight content of the second conductive agent is 0.1%-5% (for example, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%), and the weight content of the second binder is 1%-20% (for example, 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18% or 20%).
[0094] In one example, based on the total weight of the second positive electrode active layer, the sum of the weight contents of the second lithium manganese iron phosphate material and the ternary material is 93%-97.5%, the weight content of the second conductive agent is 1%-3%, and the weight content of the second binder is 1.5%-4%.
[0095] In one example, the resistivity of the positive electrode sheet is 0.2KΩ·cm-2.5KΩ·cm (for example, 0.2KΩ·cm, 0.5KΩ·cm, 1KΩ·cm, 1.5KΩ·cm, 2KΩ·cm or 2.5KΩ·cm). By controlling the resistivity of the positive electrode sheet within the above range, the resistance encountered by electrons when transmitting inside the material is small, which is beneficial to improving the charging and discharging efficiency and power output capacity of the battery, and can ensure that the electrons in the positive electrode sheet are transmitted quickly and efficiently during the charging and discharging process, thereby reducing energy loss.
[0096] In one example, the thickness of the positive electrode active material layer is 60 μm-100 μm (for example, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm). By controlling the thickness of the positive electrode active material layer within the above range, the positive electrode sheet can maintain a high energy density while also having good charge and discharge performance and cycle stability. When the thickness of the positive electrode active material layer is higher than 100 μm, although it can provide more active substances, thereby increasing the energy density of the battery, it will also increase the path length of electrons and ions transmitted inside the material, resulting in an increase in the impedance of the battery and a decrease in power output energy.
[0097] In one example, the peeling force between the first positive electrode active layer and the second positive electrode active layer is ≥ 0.05 kgf. Controlling the peeling force between the first positive electrode active layer and the second positive electrode active layer to meet the above range enables the second positive electrode active layer to be firmly attached to the first positive electrode active layer during the use of the battery, maintain the integrity of the positive electrode sheet structure, and prevent the first lithium manganese iron phosphate material from falling off due to stress during the cycle, thereby improving the cycle life of the battery. Although the peeling force value between the first positive electrode active layer and the second positive electrode active layer is smaller than the peeling force value of the first positive electrode active layer, it can still meet the needs of battery application.
[0098] A second aspect of the present invention provides a battery, comprising the positive electrode sheet according to the first aspect of the present invention.
[0099] The materials of the battery except the positive electrode sheet can be made according to the methods in the art, and can achieve the effects of higher energy density and higher safety performance.
[0100] In one example, the battery is a lithium-ion battery.
[0101] In one example, the battery further includes a negative electrode sheet and an electrolyte.
[0102] The negative electrode sheet may be a conventional negative electrode sheet in the art, for example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a negative electrode conductor and a negative electrode binder.
[0103] In one example, the negative electrode active material includes a graphite mixed material and / or graphite doped with at least one of hard carbon, soft carbon, silicon oxide and silicon carbon.
[0104] In one example, the negative electrode active material is a graphite mixed material doped with hard carbon, wherein the weight content of the hard carbon is 2wt%-10wt% (for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%) based on the total weight of the graphite mixed material.
[0105] In one example, based on the total weight of the graphite mixed material, the weight content of the hard carbon is 3wt%-5wt%.
[0106] In one example, the negative electrode conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber and carbon nanotube.
[0107] In one example, the negative electrode binder includes one or more of sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene latex, polytetrafluoroethylene, polyethylene oxide, and polyvinylidene fluoride.
[0108] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 80wt%-99.5wt% (for example, 80wt%, 85wt%, 90wt%, 95wt%, 99wt%, 99.5wt%), the weight content of the negative electrode conductor is 0.25wt%-10wt% (for example, 0.25wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%), and the weight content of the negative electrode binder is 0.25wt%-10wt% (for example, 0.25wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%).
[0109] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 90wt%-99wt%, the weight content of the negative electrode conductor is 0.5wt%-5wt%, and the weight content of the negative electrode binder is 0.5wt%-5wt%.
[0110] The electrolyte may be a conventional electrolyte in the art, for example, the electrolyte includes a lithium salt, an organic solvent and an additive.
[0111] In one example, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB) and lithium tetrafluoroborate (LiBF4).
[0112] In one example, the organic solvent includes one or more of ethylene carbonate (EC), diethyl carbonate (DEC), propyl propionate, ethyl propionate, ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and propylene carbonate (PC).
[0113] In one example, the additive includes one or more of vinylene carbonate (VC), 1,3-propane sultone (PS), 1,3-acrylonitrile lactone (PST), vinyl ethylene carbonate (VEC), succinonitrile (SN) and 1,3,6-hexanetrinitrile (HTCN).
[0114] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 5%-25% (for example, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 23% or 25%), the weight content of the organic solvent is 70%-88% (for example, 70%, 73%, 75%, 78%, 80%, 83%, 85% or 88%), and the weight content of the additive is 3%-20% (for example, 3%, 5%, 8%, 10%, 13%, 15%, 18% or 20%).
[0115] The electrolyte may be a conventional electrolyte in the art, for example, the electrolyte includes a lithium salt, an organic solvent and an additive.
[0116] In one example, the lithium salt includes one of lithium hexafluorophosphate (LiPF6), lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB) and lithium tetrafluoroborate (LiBF4).
[0117] In one example, the organic solvent includes a mixture of one or more of diethyl carbonate (DEC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and propylene carbonate (PC).
[0118] In one example, the additive includes one or more of ethylene carbonate (FEC), vinylene carbonate (VC), 1,3-propane sultone (PS), 1,3-acrylonitrile lactone (PST), vinyl ethylene carbonate (VEC), succinonitrile (SN) and 1,3,6-hexanetrinitrile (HTCN).
[0119] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 10%-20% (for example, 10%, 13%, 15%, 18% or 20%), the weight content of the organic solvent is 70%-89% (for example, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 88% or 89%), and the weight content of the additive is 1%-10% (for example, 1%, 3%, 5%, 8% or 10%).
[0120] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 11%-15%, the weight content of the organic solvent is 79%-86%, and the weight content of the additive is 3%-6%.
[0121] Since the battery of the present invention includes the positive electrode sheet described in the first aspect of the present invention, the energy density of the battery is relatively high and the needle puncture safety performance is improved.
[0122] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0123] The following examples are used to illustrate the positive electrode sheet of the present invention.
[0124] Example 1
[0125] (1) Preparation of ingredients
[0126] Positive electrode current collector: aluminum foil;
[0127] First positive electrode active layer: first lithium manganese iron phosphate material (first lithium manganese iron phosphate material including doping elements, chemical formula: LiFe 0.4 Mn 0.6 PO4, olivine structure, median particle size D1 is 0.8μm, wherein the weight content of Mg element is 3430ppm, the weight content of Ti element is 700ppm, and the weight content of Zr element is 300ppm) 92 parts by weight, first conductive agent: carbon nanotubes (length L is 60μm) 2 parts by weight, carbon black 2 parts by weight, a total of 4 parts by weight (the weight ratio of the conductive material (carbon black) to the weight of the carbon nanotubes is 1:1), first binder: PVDF, 4 parts by weight;
[0128] Second positive electrode active layer: second lithium manganese iron phosphate material (a second lithium manganese iron phosphate material including doping elements, chemical formula: LiFe 0.4 Mn 0.6 PO4, olivine structure, wherein the weight content of Mg element is 3430ppm, the weight content of Ti element is 700ppm, and the weight content of Zr element is 300ppm) and ternary material (with coating layer, chemical formula: Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, single crystal structure, the weight content A of element Al is 1000ppm, the weight content B of element Zr is 3000ppm, the weight content C of element W is 800ppm, and the weight content D of element Sr is 700ppm) totaling 96 parts by weight (wherein the weight ratio of the ternary material to the second lithium manganese iron phosphate material is 2.3), the second conductive agent: 1.2 parts by weight of conductive carbon black and 1.2 parts by weight of carbon nanotubes, totaling 2.4 parts by weight, the second binder: 1.6 parts by weight of PVDF;
[0129] (2) Preparation of positive electrode
[0130] The first lithium manganese iron phosphate, the first conductive agent, the first binder and the solvent N-methylpyrrolidone (NMP) are uniformly mixed to obtain a first positive electrode active slurry, and the first positive electrode active slurry is uniformly coated on the surfaces of both sides of the positive electrode current collector with a coating thickness of 6 μm, and then dried to obtain a first positive electrode active layer; wherein the peeling force F between the first positive electrode active layer and the positive electrode current collector is 0.6 kgf, (D1*L) / F=(0.8*60) / 0.6=80, and the surface resistance of the first positive electrode active layer is 0.1Ω;
[0131] The second lithium manganese iron phosphate, the second conductive agent, the second binder and the solvent N-methylpyrrolidone (NMP) are uniformly mixed to obtain a second positive electrode active slurry, and the second positive electrode active slurry is uniformly coated on the first positive electrode active layer, and dried to obtain the desired positive electrode sheet. Among them, A*C / (B*D)=1000*800 / (3000*700)=0.38, the thickness of the positive electrode active material layer is 80μm, and the resistivity of the positive electrode sheet is 0.37KΩ·cm.
[0132] The SEM image of the surface of the first positive electrode active layer of Example 1 is shown in Figure 6 and Figure 7 , the SEM image of the positive electrode surface after rolling is shown in Figure 8 , see the SEM image of the interface of the positive electrode. Fig.12 .
[0133] Example 2
[0134] (1) Preparation of ingredients
[0135] Positive electrode current collector: aluminum foil;
[0136] First positive electrode active layer: first lithium manganese iron phosphate material (first lithium manganese iron phosphate material including doping elements, chemical formula: LiFe 0.3 Mn 0.7 PO4, olivine structure, median particle size D1 is 1.3μm, of which the weight content of Mg element is 2671ppm, the weight content of Ti element is 538ppm, and the weight content of Zr element is 624ppm) 92 parts by weight, the first conductive agent: carbon nanotubes (length L is 73μm) 1.6 parts by weight, carbon black 2.4 parts by weight, a total of 4 parts by weight (the weight ratio of the conductive material (carbon black) to the weight of the carbon nanotubes is 1.5:1), the first binder: PVDF, 4 parts by weight;
[0137] Wherein, the thickness of the first positive electrode active layer is 8.5 μm, the peeling force F between the first positive electrode active layer and the positive electrode current collector is 0.46 kgf, (D1*L) / F=(1.3*73) / 0.46=206.3, and the surface resistance of the first positive electrode active layer is 0.13 Ω;
[0138] Second positive electrode active layer: second lithium manganese iron phosphate material (a second lithium manganese iron phosphate material including doping elements, chemical formula: LiFe 0.3 Mn 0.7 PO4, olivine structure, wherein the weight content of Mg element is 2671ppm, the weight content of Ti element is 538ppm, and the weight content of Zr element is 624ppm) and ternary material (with coating layer, chemical formula: Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, single crystal structure, the weight content A of element Al is 1181ppm, the weight content B of element Zr is 2753ppm, the weight content C of element W is 942ppm, and the weight content D of element Sr is 846ppm) totaling 96 parts by weight (wherein the weight ratio of the ternary material to the second lithium manganese iron phosphate material is 3.2), the second conductive agent: 1.2 parts by weight of conductive carbon black and 1.2 parts by weight of carbon nanotubes, totaling 2.4 parts by weight, the second binder: 1.6 parts by weight of PVDF;
[0139] Among them, A*C / (B*D)=1181*942 / (2753*846)=0.48, the thickness of the positive electrode active material layer is 60 μm, and the resistivity of the positive electrode sheet is 0.39 KΩ·cm.
[0140] (2) The positive electrode sheet was prepared in accordance with Example 1.
[0141] Example 3
[0142] (1) Preparation of ingredients
[0143] Positive electrode current collector: aluminum foil;
[0144] First positive electrode active layer: first lithium manganese iron phosphate material (first lithium manganese iron phosphate material including doping elements, chemical formula: LiFe 0.1 Mn 0.9 PO4, olivine structure, median particle size D1 is 1.8μm, of which the weight content of Mg element is 5464ppm, the weight content of Ti element is 400ppm, and the weight content of Zr element is 200ppm) 92 parts by weight, the first conductive agent: carbon nanotubes (length L is 30μm) 1.3 parts by weight, carbon black 2.7 parts by weight, a total of 4 parts by weight (the weight ratio of the conductive material (carbon black) to the weight of the carbon nanotubes is 2:1), the first binder: PVDF, 4 parts by weight;
[0145] Wherein, the thickness of the first positive electrode active layer is 2 μm, the peeling force F between the first positive electrode active layer and the positive electrode current collector is 0.77 kgf, (D1*L) / F=(1.8*30) / 0.77=70.1, and the surface resistance of the first positive electrode active layer is 0.11 Ω;
[0146] Second positive electrode active layer: second lithium manganese iron phosphate material (a second lithium manganese iron phosphate material including doping elements, chemical formula: LiFe 0.1 Mn 0.9 PO4, olivine structure, wherein the weight content of Mg element is 5464ppm, the weight content of Ti element is 400ppm, and the weight content of Zr element is 200ppm) and ternary material (with coating layer, chemical formula: Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, single crystal structure, the weight content A of element Al is 933ppm, the weight content B of element Zr is 3265ppm, the weight content C of element W is 859ppm, and the weight content D of element Sr is 917ppm) totaling 96 parts by weight (wherein the weight ratio of the ternary material to the second lithium manganese iron phosphate material is 1.4), the second conductive agent: 1.2 parts by weight of conductive carbon black and 1.2 parts by weight of carbon nanotubes, totaling 2.4 parts by weight, the second binder: 1.6 parts by weight of PVDF;
[0147] Among them, A*C / (B*D)=933*859 / (3265*917)=0.27, the thickness of the positive electrode active material layer is 100 μm, and the resistivity of the positive electrode sheet is 0.38 KΩ·cm.
[0148] (2) The positive electrode sheet was prepared in accordance with Example 1.
[0149] Example 4 Group
[0150] This group of embodiments is used to illustrate the impact when a changes.
[0151] Example 4a
[0152] The method is carried out in accordance with Example 1, except that a in the first lithium manganese iron phosphate material is 0.7, a in the second lithium manganese iron phosphate material is 0.7, and the resistivity of the positive electrode sheet is 0.39 KΩ·cm.
[0153] Example 4b
[0154] The method is carried out in accordance with Example 1, except that a in the first lithium manganese iron phosphate material is 0.2, a in the second lithium manganese iron phosphate material is 0.2, and the resistivity of the positive electrode sheet is 0.38 KΩ·cm.
[0155] Example 4c
[0156] The method is carried out in accordance with Example 1, except that a in the first lithium manganese iron phosphate material is 0.4, a in the second lithium manganese iron phosphate material is 0.7, and the resistivity of the positive electrode sheet is 0.37 KΩ·cm.
[0157] Example 4d
[0158] The method is carried out in accordance with Example 1, except that a in the first lithium manganese iron phosphate material is 0.7, a in the second lithium manganese iron phosphate material is 0.4, and the resistivity of the positive electrode sheet is 0.39 KΩ·cm.
[0159] Example 5 Group
[0160] This group of embodiments is used to illustrate the impact produced when the weight content of the doping element in the first lithium manganese iron phosphate material changes.
[0161] Example 5a
[0162] The process is carried out in accordance with Example 1, except that the weight content of the Mg element is 1500 ppm and the resistivity of the positive electrode sheet is 0.38 KΩ·cm.
[0163] Example 5b
[0164] The same method is carried out as in Example 1, except that the weight content of the Mg element is 4500 ppm and the resistivity of the positive electrode sheet is 0.37 KΩ·cm.
[0165] Example 5c
[0166] The process is carried out in accordance with Example 1, except that the weight content of the Mg element is 500 ppm and the resistivity of the positive electrode sheet is 0.38 KΩ·cm.
[0167] Example 5d
[0168] The same method is carried out as in Example 1, except that the weight content of the Mg element is 6000 ppm and the resistivity of the positive electrode sheet is 0.39 KΩ·cm.
[0169] Example 5e
[0170] The same process is carried out as in Example 1, except that the weight content of Mg element is 430 ppm.
[0171] Example 5f
[0172] The process is carried out in accordance with Example 1, except that the weight content of the Mg element is 6700 ppm and the resistivity of the positive electrode sheet is 0.38 KΩ·cm.
[0173] Example 5g
[0174] The same method is carried out as in Example 1, except that the weight content of the T element is 1000 ppm, the weight content of the Zr element is 700 ppm, and the resistivity of the positive electrode sheet is 0.39 KΩ·cm.
[0175] Example 6 Group
[0176] This group of embodiments is used to illustrate the impact produced when the ratio of the weight of the conductive material to the weight of the carbon nanotubes is changed.
[0177] Example 6a
[0178] The same method is used as in Example 1, except that the weight of the first conductive agent is kept unchanged, the weight content of carbon nanotubes in the first positive electrode active layer is 1.3%, the ratio of the weight of the conductive material to the weight of the carbon nanotubes is 2:1, and the surface resistance of the first positive electrode active layer is 0.11Ω.
[0179] Example 6b
[0180] The method is carried out in accordance with Example 1, except that the weight of the first conductive agent is kept unchanged, the weight content of carbon nanotubes in the first positive electrode active layer is 2.7%, the ratio of the weight of the conductive material to the weight of the carbon nanotubes is 0.5:1, the surface resistance of the first positive electrode active layer is 0.24Ω, and the resistivity of the positive electrode sheet is 0.4KΩ·cm.
[0181] Example 6c
[0182] The same method is used as in Example 1, except that the weight of the first conductive agent is kept unchanged, the weight content of carbon nanotubes in the first positive electrode active layer is 0.5%, the ratio of the weight of the conductive material to the weight of the carbon nanotubes is 7:1, and the surface resistance of the first positive electrode active layer is 0.13Ω.
[0183] Example 6d
[0184] The method is carried out in accordance with Example 1, except that the weight of the first conductive agent is kept unchanged, the weight content of carbon nanotubes in the first positive electrode active layer is 3%, the ratio of the weight of the conductive material to the weight of the carbon nanotubes is 0.3:1, the surface resistance of the first positive electrode active layer is 0.26Ω, and the resistivity of the positive electrode sheet is 0.42KΩ·cm.
[0185] Example 6e
[0186] The process is carried out in accordance with Example 1, except that the weight of the first conductive agent is kept unchanged, the weight content of the carbon nanotubes in the first positive electrode active layer is 0.2%, the ratio of the weight of the conductive material to the weight of the carbon nanotubes is 19:1, the surface resistance of the first positive electrode active layer is 0.35Ω, and the resistivity of the positive electrode sheet is 0.52KΩ·cm.
[0187] Example 6f
[0188] The process was carried out in accordance with Example 1, except that the weight of the first conductive agent was kept unchanged, the weight content of carbon nanotubes in the first positive electrode active layer was 3.5%, the ratio of the weight of the conductive material to the weight of the carbon nanotubes was 0.14:1, the surface resistance of the first positive electrode active layer was 0.3Ω, and the resistivity of the positive electrode sheet was 0.45KΩ·cm.
[0189] Example 7 Group
[0190] This group of embodiments is used to illustrate the impact when (D1*L) / F changes.
[0191] Example 7a
[0192] The same process is carried out as in Example 1, except that D1 is 0.5 μm and (D1*L) / F=50.
[0193] Example 7b
[0194] Refer to Example 1, except that D1 is 1.5 μm, L is 70 μm, F=0.3 kgf, (D1*L) / F=350, the surface resistance of the first positive electrode active layer is 0.13 Ω, and the resistivity of the positive electrode sheet is 0.36 KΩ·cm.
[0195] Example 7c
[0196] The same method is used as in Example 1, except that D1 is 0.2 μm, (D1*L) / F=20, the surface resistance of the first positive electrode active layer is 0.14 Ω, and the resistivity of the positive electrode sheet is 0.4 KΩ·cm.
[0197] Example 7d
[0198] The same procedure is carried out as in Example 1, except that D1 is 2 μm, F=0.3 kgf, (D1*L) / F=400, and the resistivity of the positive electrode is 0.38 KΩ·cm.
[0199] Example 7e
[0200] The same procedure is carried out as in Example 1, except that L is 80 μm, F=0.9 kgf, (D1*L) / F=71.1, and the resistivity of the positive electrode is 0.39 KΩ·cm.
[0201] Example 7f
[0202] Refer to Example 1, except that D1 is 2 μm, L is 5 μm, F=0.3 kgf, (D1*L) / F=33.3, the surface resistance of the first positive electrode active layer is 0.17 Ω, and the resistivity of the positive electrode sheet is 0.42 KΩ·cm.
[0203] Example 7g
[0204] Refer to Example 1, except that D1 is 2 μm, L is 80 μm, F=0.7 kgf, (D1*L) / F=228.6, the surface resistance of the first positive electrode active layer is 0.13 Ω, and the resistivity of the positive electrode sheet is 0.38 KΩ·cm.
[0205] Example 7h
[0206] The same procedure is carried out as in Example 1, except that F=1.7 kgf and (D1*L) / F=28.2.
[0207] Example 7i
[0208] The same process is carried out as in Example 1, except that D1 is 2 μm, L is 90 μm, F=0.4 kgf, and (D1*L) / F=450.
[0209] Embodiment 7j
[0210] The same process is carried out as in Example 1, except that L is 80 μm, F=0.2 kgf, and (D1*L) / F=320.
[0211] Embodiment 7k
[0212] The same method is carried out as in Example 1, except that L is 110 μm, F=0.9 kgf, (D1*L) / F=97.8, the surface resistance of the first positive electrode active layer is 0.13 Ω, and the resistivity of the positive electrode sheet is 0.41 KΩ·cm.
[0213] Embodiment 71
[0214] Refer to Example 1, except that D1 is 0.15 μm, L is 70 μm, F=0.3 kgf, (D1*L) / F=35, the surface resistance of the first positive electrode active layer is 0.14 Ω, and the resistivity of the positive electrode sheet is 0.43 KΩ·cm.
[0215] Example 7m
[0216] Refer to Example 1, except that D1 is 3 μm, L is 80 μm, F=0.7 kgf, (D1*L) / F=342.9, the surface resistance of the first positive electrode active layer is 0.13 Ω, and the resistivity of the positive electrode sheet is 0.42 KΩ·cm.
[0217] Example 8 Group
[0218] This group of embodiments is used to illustrate the impact produced when the weight content of the doping element in the second lithium manganese iron phosphate material changes.
[0219] Example 8a
[0220] The process is carried out in accordance with Example 1, except that the weight content of the Mg element is 1500 ppm and the resistivity of the positive electrode sheet is 0.38 KΩ·cm.
[0221] Example 8b
[0222] The same process is carried out as in Example 1, except that the weight content of Mg element is 4500 ppm.
[0223] Example 8c
[0224] The same method is carried out as in Example 1, except that the weight content of the Mg element is 500 ppm and the resistivity of the positive electrode sheet is 0.39 KΩ·cm.
[0225] Example 8d
[0226] The process is carried out in accordance with Example 1, except that the weight content of the Mg element is 6000 ppm and the resistivity of the positive electrode sheet is 0.38 KΩ·cm.
[0227] Example 8e
[0228] The same process is carried out as in Example 1, except that the weight content of Mg element is 430 ppm.
[0229] Example 8f
[0230] The process is carried out in accordance with Example 1, except that the weight content of the Mg element is 6700 ppm and the resistivity of the positive electrode sheet is 0.38 KΩ·cm.
[0231] Example 8g
[0232] The same process is carried out as in Example 1, except that the weight content of the T element is 1000 ppm and the weight content of the Zr element is 700 ppm.
[0233] Example 9 Group
[0234] This group of embodiments is used to illustrate the impact when the weight ratio of the ternary material to the second lithium manganese iron phosphate material changes.
[0235] Example 9a
[0236] The method is carried out in accordance with Example 1, except that the weight ratio of the ternary material to the weight of the second lithium manganese iron phosphate material is 1, and the resistivity of the positive electrode sheet is 0.42 KΩ·cm.
[0237] Example 9b
[0238] The method is carried out in accordance with Example 1, except that the weight ratio of the ternary material to the second lithium manganese iron phosphate material is 4, and the resistivity of the positive electrode sheet is 0.35 KΩ·cm.
[0239] Example 9c
[0240] The method is carried out in accordance with Example 1, except that the weight ratio of the ternary material to the second lithium manganese iron phosphate material is 0.5, and the resistivity of the positive electrode sheet is 0.56 KΩ·cm.
[0241] Example 9d
[0242] The method is carried out in accordance with Example 1, except that the weight ratio of the ternary material to the second lithium manganese iron phosphate material is 5, and the resistivity of the positive electrode sheet is 0.35 KΩ·cm.
[0243] Example 10 Group
[0244] This group of embodiments is used to illustrate the impact when A*C / (B*D) changes.
[0245] Example 10a
[0246] The same procedure was followed as in Example 1, except that A was 800 ppm, B was 3000 ppm, C was 700 ppm, D was 700 ppm, and A*C / (B*D)=0.27.
[0247] Example 10b
[0248] The same method is used as in Example 1, except that A is 1200 ppm, B is 3000 ppm, C is 1000 ppm, D is 700 ppm, A*C / (B*D)=0.57, and the resistivity of the positive electrode is 0.38 KΩ·cm.
[0249] Example 10c
[0250] The same procedure was followed as in Example 1, except that A was 1200 ppm, B was 2500 ppm, C was 1000 ppm, D was 600 ppm, and A*C / (B*D)=0.8.
[0251] Example 10d
[0252] Refer to Example 1, except that A is 800 ppm, B is 3500 ppm, C is 700 ppm, D is 1000 ppm, A*C / (B*D)=0.16, and the resistivity of the positive electrode is 0.38 KΩ·cm.
[0253] Example 10e
[0254] The same process was carried out as in Example 1, except that A was 720 ppm, B was 2500 ppm, C was 1000 ppm, D was 600 ppm, and A*C / (B*D)=0.48.
[0255] Example 10f
[0256] Refer to Example 1, except that A is 500 ppm, B is 3500 ppm, C is 400 ppm, D is 1000 ppm, A*C / (B*D)=0.06, and the resistivity of the positive electrode is 0.36 KΩ·cm.
[0257] Example 10g
[0258] The same procedure was followed as in Example 1, except that A was 1400 ppm, B was 2500 ppm, C was 1200 ppm, D was 600 ppm, and A*C / (B*D)=1.12.
[0259] Embodiment 11
[0260] The process is carried out in accordance with Example 1, except that the ternary material is polycrystalline and the resistivity of the positive electrode sheet is 0.39 KΩ·cm.
[0261] Comparative Example 1
[0262] The process was carried out in accordance with Example 1, except that there was no first positive electrode active layer, and the resistivity of the positive electrode sheet was 0.35 KΩ·cm.
[0263] Among them, the schematic diagram of the positive electrode sheet of Comparative Example 1 is shown in Figure 4 , the SEM image of the positive electrode surface after rolling in comparative example 1 is shown in Fig. 9 , see the SEM image of the positive electrode cross section Fig.14 .
[0264] Comparative Example 2
[0265] The method was carried out in accordance with Example 1, except that the first lithium manganese iron phosphate material was replaced with titanium dioxide, the surface resistance of the first positive electrode active layer was 0.78Ω, and the resistivity of the positive electrode sheet was 3.5KΩ·cm.
[0266] Among them, the schematic diagram of the positive electrode sheet of Comparative Example 2 is shown in Figure 1 The SEM image of the coating surface including titanium dioxide of the positive electrode sheet of Comparative Example 2 is shown in Figure 5 , the SEM image of the positive electrode surface after rolling is shown in Fig.10 , see the SEM image of the positive electrode cross section Fig.13 .
[0267] Comparative Example 3
[0268] The method is carried out in accordance with Example 1, except that the first lithium manganese iron phosphate material is replaced by titanium dioxide and the second positive electrode active layer does not have the second lithium manganese iron phosphate material. The surface resistance of the first positive electrode active layer is 0.79Ω, and the resistivity of the positive electrode sheet is 3.1KΩ·cm.
[0269] Among them, the schematic diagram of the positive electrode sheet of Comparative Example 3 is shown in Figure 2 .
[0270] Comparative Example 4
[0271] The same procedure is carried out with reference to Example 1, except that the second lithium manganese iron phosphate material is replaced with lithium iron phosphate material, and the resistivity of the positive electrode sheet is 0.37 KΩ·cm.
[0272] Comparative Example 5
[0273] The method was carried out in accordance with Example 1, except that no carbon nanotubes were added to the first positive electrode active layer. The surface resistance of the first positive electrode active layer was 0.98Ω, and the resistivity of the positive electrode sheet was 4.7KΩ·cm.
[0274] Comparative Example 6
[0275] The method was carried out in accordance with Example 1, except that no second lithium manganese iron phosphate material was added as an additive in the second positive electrode active layer, and the resistivity of the positive electrode sheet was 0.35 KΩ·cm.
[0276] Among them, the SEM image of the positive electrode surface after rolling in comparative example 6 is shown in Fig.11 , see the SEM image of the positive electrode cross section Fig.15 .
[0277] Comparative Example 7
[0278] The method is carried out in accordance with Example 1, except that the first lithium manganese iron phosphate material is replaced with lithium iron phosphate, the surface resistance of the first positive electrode active layer is 0.12Ω, and the resistivity of the positive electrode sheet is 0.37KΩ·cm.
[0279] Preparation Example
[0280] Batteries were prepared using the positive electrode materials obtained in the examples and comparative examples according to the following methods.
[0281] (1) Positive electrode
[0282] The positive electrode sheets obtained in the above-mentioned embodiments and comparative examples were used respectively.
[0283] (2) Negative electrode
[0284] The negative electrode active material (graphite), negative electrode binder (sodium carboxymethyl cellulose (CMC-Na)), negative electrode binder (styrene-butadiene latex), and negative electrode conductive agent (conductive carbon black) are mixed in a weight ratio of 97:1:1:1, deionized water is added, and negative electrode slurry is obtained under the action of a vacuum mixer; the negative electrode slurry is evenly coated on both sides of a high-strength 6μm copper foil, dried at room temperature, transferred to an oven at 80°C for 10 hours, and then rolled and cut to obtain a negative electrode sheet.
[0285] (3) Electrolyte
[0286] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), mix the organic solvent evenly, then quickly add fully dried lithium salt, dissolve it and add additives to obtain the required electrolyte. Among them, lithium salt: lithium hexafluorophosphate, 10 parts by weight; organic solvent (ethylene carbonate (EC) 40 parts by weight, diethyl carbonate (DEC) 40 parts by weight, dimethyl carbonate (DMC) 5 parts by weight) 85 parts by weight, additive (vinylene carbonate (VC)) 5 parts by weight.
[0287] (4) Diaphragm
[0288] A large-pore diaphragm is used, the base membrane pore size is between 45nm-58nm, the base membrane surface is coated with a boehmite ceramic layer and a water-based adhesive layer, the adhesive layer is a mixture of water-based PVDF (volume median diameter 0.5μm) and PMMA (volume median diameter 0.2μm) at a mass ratio of 5:5, the adhesive layer coverage is 50%, and the adhesive layer thickness is 1.5μm. The diaphragm has a porosity of 40%, an air permeability of 90sec / 100cc, a puncture strength of 280gf, a tensile strength of 1850kgf / cm2, and an adhesive force of 21N / m.
[0289] (5) Preparation of lithium-ion batteries
[0290] The positive electrode sheet of step (1), the negative electrode sheet of step (2) and the separator of step (4) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, the electrolyte of step (3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes.
[0291] Test Case
[0292] The lithium ion batteries obtained in the embodiments and comparative examples were tested as follows:
[0293] 1. Battery capacity, internal resistance, thickness and energy density test
[0294] The lithium-ion battery is charged at 0.2C current to 4.2V at 25°C, charged to full charge (100% SOC) at 0.05C at cut-off current, and then discharged to 2.5V at 0.2C. The discharged capacity is recorded as the battery capacity.
[0295] Charge the lithium-ion battery to 30% SOC at 25°C and use an internal resistance tester to test the internal resistance of the battery;
[0296] The lithium-ion battery was charged to 30% SOC at 25°C and the battery thickness was tested using 600g PPG.
[0297] Calculate volume energy density = battery capacity * platform voltage / battery length / width / thickness.
[0298] 2. Acupuncture test
[0299] After the lithium-ion battery is fully charged, needles of different diameters (4mm, 8mm) are used to completely penetrate the battery at a speed of 0.1mm / s. The battery is considered to have passed if it does not catch fire or explode. A total of 20 batteries are tested and the results are expressed as "number of passed batteries / 20". For example, if 17 out of 20 batteries pass the test, the result is expressed as "17 / 20".
[0300] 3. Hot box test
[0301] The lithium-ion battery was subjected to a hot box test at different temperatures (130°C, 140°C). The test method was as follows: After the lithium-ion battery was fully charged, it was placed on a hot box test device, and the hot box was heated at a rate of 5°C / min. After heating to the corresponding temperature, it was maintained for 60 minutes, and then the hot box temperature was lowered. The battery passed the test if it did not catch fire or explode. A total of 20 batteries were tested, and the results were expressed as "number of passed batteries / 20". For example, if 17 of the 20 batteries passed the test, the result would be expressed as "17 / 20".
[0302] 4. Cycle performance test
[0303] The lithium-ion battery is subjected to a 3C / 12C charge and discharge cycle at 35°C, 3C charging to 4.2V, cut-off current 0.05C, 12C discharge to 2.5V, and the discharge capacity at this time is recorded as the initial capacity as the first cycle. After 800 cycles, the capacity at this time is recorded as the final capacity, and the battery capacity retention rate (%) = [final capacity / initial capacity] × 100%;
[0304] Expansion rate: The initial thickness is the thickness of the incoming battery. After 800 cycles, that is, 3C charging to 4.2V, the thickness when the cut-off current is 0.05C is the final thickness. Expansion rate (%) = [final thickness / initial thickness] × 100%.
[0305] The obtained results are recorded in Table 1.
[0306] Table 1
[0307]
[0308]
[0309]
[0310]
[0311] It can be seen from Table 1 that the energy density of the battery made from the positive electrode sheet of the embodiment is higher, the safety performance is significantly improved, and the cycle capacity retention rate is significantly improved, which means that the energy density and safety performance of the battery are improved by arranging the first positive electrode active layer between the positive electrode collector and the second positive electrode active layer, and making the first positive electrode active layer and the second positive electrode active layer both include lithium iron manganese phosphate material.
[0312] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode collector and a positive electrode active material layer located on one side or both sides of the positive electrode collector, the positive electrode active material layer includes a first positive electrode active layer and a second positive electrode active layer, the first positive electrode active layer is located between the positive electrode collector and the second positive electrode active layer, the first positive electrode active layer includes a first lithium iron manganese phosphate material and a first conductive agent, the first conductive agent includes carbon nanotubes; the second positive electrode active layer includes a ternary material and a second lithium iron manganese phosphate material.
2. The positive electrode sheet according to claim 1, wherein: The positive electrode sheet satisfies the following relationship: 27.8≤(D1*L) / F≤400, wherein D1 is the median particle size Dv50 of the first lithium manganese iron phosphate material, in μm, L is the length of the carbon nanotube, in μm, and F is the peeling force between the first positive electrode active layer and the positive electrode current collector, in kgf; and / or, the median particle size D1 of the first lithium manganese iron phosphate material is 0.2 μm-2 μm, preferably 0.5 μm-1.5 μm; and / or, the length L of the carbon nanotubes is 5 μm-100 μm, preferably 50 μm-80 μm; And / or, the peeling force F between the first positive electrode active layer and the positive electrode current collector is ≥0.3 kgf, preferably 0.3 kgf-0.9 kgf.
3. The positive electrode sheet according to claim 2, wherein: The first positive electrode active layer further includes a first binder, which includes one or more of polyvinylidene fluoride, acrylic acid-modified polyvinylidene fluoride, carboxylic acid-modified polyvinylidene fluoride, polyacrylic acid, polyacrylic acid copolymer, polymethyl methacrylate, carboxylated polyvinylidene fluoride, polyvinyl alcohol and polyimide; and / or, the weight content w1 of the carbon nanotubes in the first positive electrode active layer is 0.2%-3%, preferably 0.5%-2%; And / or, the weight content w3 of the first binder in the first positive electrode active layer is 2%-7%, preferably 2.5%-5%.
4. The positive electrode sheet according to any one of claims 1 to 3, wherein: The ternary material comprises a chemical formula of Li(Ni x Co y Mn z )O2 material, wherein x+y+z=1, 0.8≤x<1, 0<y<0.2, 0<z<0.2; And / or, the surface of the ternary material has a coating layer, the coating layer includes metal oxides, the metal oxides include Al2O3, ZrO2, WO3 and SrO, then the ternary material satisfies the following relationship: 0.16≤A*C / (B*D)≤0.8, wherein A is the weight content of element Al in the ternary material with the coating layer, in ppm, B is the weight content of element Zr in the ternary material with the coating layer, in ppm, C is the weight content of element W in the ternary material with the coating layer, in ppm, and D is the weight content of element Sr in the ternary material with the coating layer, in ppm, wherein the range of A is 800ppm-1200ppm, the range of B is 2500ppm-3500ppm, the range of C is 700ppm-1000ppm, and the range of D is 600ppm-1000ppm.
5. The positive electrode sheet according to any one of claims 1 to 3, wherein: The ternary material comprises a single crystal structure; And / or, the median particle size Dv50 of the ternary material is 2 μm-5 μm; And / or, the median particle size Dv50 of the second lithium manganese iron phosphate material is 0.5 μm-1.5 μm.
6. According to any one of claims 1 to 3, the positive electrode sheet, the weight ratio of the ternary material to the weight of the second lithium manganese iron phosphate material is (1-4):
1.
7. The positive electrode sheet according to any one of claims 1 to 3, wherein: The first lithium iron manganese phosphate material and the second lithium iron manganese phosphate material each independently include a chemical formula of LiFe a Mn (1-a) PO4 material, wherein 0<a<1, preferably 0.2≤a≤0.4; And / or, the first lithium iron manganese phosphate material and / or the second lithium iron manganese phosphate material include doping elements, the doping elements include Mg, Ti and Zr, and based on the total weight of the first lithium iron manganese phosphate material including the doping elements, the weight content of the Mg element is 1500ppm-4500ppm, the weight content of the Ti element is 400ppm-1000ppm, and the weight content of the Zr element is 200ppm-700ppm; based on the total weight of the second lithium iron manganese phosphate material including the doping elements, the weight content of the Mg element is 1500ppm-4500ppm, the weight content of the Ti element is 400ppm-1000ppm, and the weight content of the Zr element is 200ppm-700ppm.
8. The positive electrode sheet according to any one of claims 1 to 3, wherein: The surface resistance of the first positive electrode active layer is 0.01Ω-0.4Ω; And / or, the resistivity of the positive electrode sheet is 0.2KΩ·cm-2.5KΩ·cm.
9. The positive electrode sheet according to any one of claims 1 to 3, wherein: The thickness of the first positive electrode active layer is 2 μm-10 μm; And / or, the thickness of the positive electrode active material layer is 60 μm-100 μm.
10. A battery, characterized in that: The battery comprises the positive electrode sheet according to any one of claims 1 to 9.
Citation Information
Patent Citations
Pole piece and preparation method thereof
CN115360325A
Nickel cobalt lithium manganate positive electrode material, and preparation method and application thereof
CN115632118A
Lithium manganese iron phosphate composite material as well as preparation method and application thereof
CN116470030A
Positive plate and battery
CN116979016A
Positive plate and lithium ion battery
CN117334830A
Cited By
Positive plate and lithium ion secondary battery
CN120072849A
Positive plate, battery, battery pack and electric equipment
CN120600749A